Kinetics of poly(ADP-ribosyl)ation, but not PARP1 itself, determines the cell fate in response to DNA damage in vitro and in vivo. Issue 19 (18th August 2017) - Schuhwerk, Harald; Bruhn, Christopher; Siniuk, Kanstantsin; Min, Wookee; Erener, Suheda; Grigaravicius, Paulius; Krüger, Annika; Ferrari, Elena; Zubel, Tabea; Lazaro, David; Monajembashi, Shamci; Kiesow, Kirstin; et al.
Abstract: One of the fastest cellular responses to genotoxic stress is the formation of poly(ADP-ribose) polymers (PAR) by poly(ADP-ribose)polymerase 1 (PARP1, or ARTD1). PARP1 and its enzymatic product PAR regulate diverse biological processes, such as DNA repair, chromatin remodeling, transcription and cell death. However, the inter-dependent function of the PARP1 protein and its enzymatic activity clouds the mechanism underlying the biological response. We generated a PARP1 knock-in mouse model carrying a point mutation in the catalytic domain of PARP1 (D993A), which impairs the kinetics of the PARP1 activity and the PAR chain complexity in vitro and in vivo, designated as hypo-PARylation. PARP1 D993A/D993A mice and cells are viable and show no obvious abnormalities. Despite a mild defect in base excision repair (BER), this hypo-PARylation compromises the DNA damage response during DNA replication, leading to cell death or senescence. Strikingly, PARP1 D993A/D993A mice are hypersensitive to alkylation in vivo, phenocopying the phenotype of PARP1 knockout mice. Our study thus unravels a novel regulatory mechanism, which could not be revealed by classical loss-of-function studies, on how PAR homeostasis, but not the PARP1 protein, protects cells and organisms from acute DNA damage.